The extent of the standers of quality achieved in the basic elements of the curriculum of the general teaching methods in the college of Basic Education from the points of view of teachers of the subject. - سعدون صالح مطر / ضياء عويد العرنوسي ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The present study deals with the quality standers that should be found in the curriculum of general teaching methods from the points of view of the teachers at the basic education college so as to know where could we determine some defects in the building of such criterion in the curriculum in order to make some remedies for these defects .The researchers apply questionnaire to gather the appropriate information that related to the results of this study. The questionnaire includes the following area :curriculum philosophy, aims, methods and evaluation. The sample of the study consists of 25 teachers who they are chosen from the original population in random method. The results of this study shows there are some defects in the building of some criterion especially in the contents and aims of the curriculum. On the base of these results some conclusions are made and some recommendation are drawn